Late Campanian larger benthic foraminifera from the Zekeriyakiiy Formation (Istanbul, NW Turkey): taxonomy, stratigraphy, and paleogeography - Erdem, Mert Eren; Ozcan, Ercan; Yucel, Ali Osman; Okay, Aral, I; Erbay, Sadikcan; Kaygili, Sibel; Yilmaz, Isak (Tubitak Scientific & Technological Research Council Turkey, 2021)
North of Istanbul, the thick Upper Cretaceous volcanic and volcanoclastic sequence of the Yemislicay Group is nonconformably overlain by the neritic clastic and carbonate sequence of the Zekeriyakoy Formation. This unit, either placed within the volcanic sequence or interpreted to overlie it, was studied near Zekeriyakoy for its larger foraminifera, previously recurrently referred to as the Maastrichtian. The basal epiclastic sandstone beds of the Zekeriyakoy Formation immediately above the volcanic sequence contain Praesiderolites dordoniensis and rare rudist shells. The higher sandstone and limestone beds comprise assemblages of Lepidorbitoides campaniensis, Orbitoides megaloformis, Vanderbeekia catalana, Siderolites gr. calcitrapoides, Sirtina orbitoidiformis, Praestorrsella roestae, Lenticulina rotulata, Planorbulina sp., agglutinated and rotaliid foraminifera, rudist fragments, bryozoans, and red algae. Lepidorbitoides, the most abundant foraminifera in the studied material, has predominantly L. campaniensis-type embryons with a single auxiliary chamberlet, and rarely, L. bisambergensis-type embryons, characterized by having 2 such chamberlets. The Praesiderolites dordoniensisLepidorbitoides campaniensis-Vanderbeekia catalana assemblages, recorded for the first time in Turkey, suggested a late Campanian age for the Zekeriyakoy Formation, with the implication that Late Cretaceous volcanism terminated in the Istanbul region during or prior to the late Campanian. The fauna shows a great resemblance to those from the Late Campanian type-section in Aubeterre (SW France) and Late Campanian fauna of the Pyrenean Basin (N Spain), and correspond to the most eastern record of the European Faunal Province of the Tethys.
Keywords: Larger benthic foraminifera; Late Campanian; northwestern Turkey; systematics